TECHNICAL FEATURES OF RIGGED YACHT BY CATEGORIES AND CLASSES - Yeroshkina , S.G. (The actual problems of regional economy development, 2016)
The article is directed on the deeply meaningful scientific study and structural analysis of the technical features of the rigged world modern yachts to pass sailing regattas in different navigation areas. The complete classification of sailing boats in it’s world classes was done for olympic, international, national regattas. It was done the technical indicators of yachting racing classes. The economic analysis material selection sails for yachts are directed of different types of races. In it’s scientific article is made economic calculation of operating cost of the boat and it was done the analysis of cost saving yachts in european / ukrainian marinas. JEL: L 92